Development of Drone Real-time Air Pollution Monitoring for Mobile Smart Sensing in Areas with Poor Accessibility - Sarun Duangsuwan; Punyawi Jamjareekulgarn (My University, 2020)
The topic of air pollution, especially in terms of particulate matter (PM), is a very serious problem in current society.This problem is caused by such factors as forest fires, construction, industrialization, and the ever-increasing number of motor vehicles.Thus, PM 2.5 has become an important risk factor for citizens in Thailand as well as globally, not only in terms of the problems associated with health risks, but also the negative impact on the image of the country.Measuring pollution for air quality monitoring is a challenging task, especially when considering areas that have poor accessibility.The aim of this work is to develop a drone equipped with sensors to monitor and collect air quality data in real time from such areas of potential pollution.The proposed drone is called the drone for real-time air pollution monitoring (Dr-TAPM) and is equipped with the ability to measure the concentration of carbon monoxide (CO), ozone (O 3 ), nitrogen dioxide (NO 2 ), PM, and sulfur dioxide (SO 2 ).Additionally, the collected data is transmitted to a cloud server every second over a wireless internet connection.In this study, the measurement was conducted in the experiment area, which is considered to be in the pollutant model scenario.The experimental results are shown as graphs of quantitative pollutant levels and air quality index (AQI) values obtained from realtime monitoring on a mobile application.
Keywords: Drone; Air Quality Monitoring and Forecasting